Development of Seaweed (Padina tetrastromatica) incorporated Mince Sausage from Common Carp (Cyprinus carpio), reared in Inland Saline Water - Dharani M.; Amjad Khansaheb Balange (Journal of Indian Fisheries Association, 2023)
The study was conducted for the development of seaweed based value-added product from inland saline water-reared common carp fish mince. Three concentrations of seaweed powder (0.5%, 1%, and 2%) were used. The addition of 2% P. tetrastromatica powder to mince showed better results as compared to other treatments. Compared to control sausages with 0% seaweed inclusion, the common carp mince sausages with 2% seaweed powder addition had greater hardness values and ash content. Additionally, the sensory scores of the sausages that contain seaweed powder were satisfactory. Therefore, seaweed powder can be utilised as a potential component to enhance the dietary value and textural properties of fish mince sausages. Furthermore, developing value-added products will boost the market value of fish raised in inland saltwater, which are underutilised resources with a significant potential to expand aquaculture production.